AKROTHINIA Contributi di giovani ricercatori italiani agli studi egei e ciprioti - Jasink, Anna Margherita; Bombardieri, Luca (Strumenti per la didattica e la ricerca, 2015)
Akrothinia collects the contributions of twenty-three young scholars, with the aim of creating an overall picture of the lines of investigation and of the interests which, in recent years, have animated research in the field of Prehistory and Protohistory of the Aegean area, as seen from the perspective of 'pupils', not of 'masters'. The broad horizon of archaeological and philological themes, as well as the new insights which can be noticed in the works of this volume, clearly demonstrate the liveliness and, at the same time, the value of the tradition of Aegean studies in Italy. In this sense, the common thread linking all the contributions is, on one hand, the balance between the value recognized by the authors and the long tradition of Italian studies and, on the other, the positive interest in projects used as a test for the ability to identify new prospects for investigation.